Clinical Evaluation of Sequential Transdermal Delivery of Vitamin B6, Compound Glycyrrhizin, Metronidazole, and Hyaluronic Acid Using Needle-Free Liquid Jet in Facial Seborrheic Dermatitis - Zhang, Xiaomin; Luo, Bizhu; Mo, Huihui; Liao, Lexi; Wang, Shuai; Du, Juan; Liu, Qiuting; Liang, Yanhua (Frontiers in Medicine, 2020)
Facial seborrheic dermatitis (FSD) is a common facial inflammatory dermatitis. Needle-free transdermal jet injection (NTJI) is a non-invasive and painless injection of drug solution by using high-pressure liquid injection instrument. The aim of this study was to explore a safer, more tolerable and convenient medical way using NTJI in the treatment of FSD. This was a retrospective study. The FSD patients were treated with vitamin B6, Glycyrrhizin compound, metronidazole and hyaluronic acid using NTJI, and only those for more than 3 times were included. To elucidate the efficacy of the treatment, two different objective indicators were used: a VISIA facial imaging system for the evaluation of erythema, superficial lipid level (SLL) and roughness of skin surface (RSS) and a CK analyzer for biophysical parameter including the stratum corneum hydration (SCH), facial surface lipid (FSL) and trans-epidermal water loss (TEWL). Investigator Global Assessment (IGA) Score and patient’s self-assessment were taken as the subjective assessments. Based on the inclusion and exclusion criteria, 72 FSD patients were finally included from the 374 patient pool. Erythema was significantly reduced after every treatment (week 2, week 4 and week 6; P<0.05), while SLL was not improved significantly until week 6 (P<0.05), and RSS was not improved significantly during the whole treatment, implicating the rapidest improvement on local inflammation. The SCH of lesional skin was significantly increased after 3 times of treatment (P<0.05), while FSL and TEWL were not improved significantly. The IGA Score was deceased significantly at week 4 and week 6 (P<0.05). Twenty-two patients (31 %) expressed a remarkable improvement, 31 (43 %) good, 12 (17 %) moderate and 7 (9 %) poor. A recurrence rate of FSL in 56% patients, but no relapse of any other symptom, was observed at the 4-weeks follow-up visit. No observable adverse effect, such as marked erythema, blistering, or atrophy, was observed. Sequential transdermal delivery of small molecular weight drugs (vitamin B6, Glycyrrhizin compound, metronidazole and hyaluronic acid) using NTJI is a safe, low- toxicity, and take-home drug free therapy for the treatment of FSD.